An optimised approach for continuous-flow solid-phase peptide synthesis utilising a rudimentary flow reactor. Issue 6 (2nd October 2018) - Spare, Lawson K.; Laude, Victoire; Harman, David G.; Aldrich-Wright, Janice R.; Gordon, Christopher P.
Abstract : From the repurposing of used HPLC components, a chromatography column, a Rheodyne, ® and a heater stirrer, a simple, cost-effective system to conveniently conduct continuous flow solid-phase peptide construction was assembled. Abstract : From the repurposing of used HPLC components, a chromatography column, a Rheodyne, ® and a heater stirrer, a simple, cost-effective system to conveniently conduct continuous flow solid-phase peptide construction was assembled. Through the utilisation of this rudimentary system, the first systematic study comparing and contrasting key parameters such as resin matrices, temperatures, flow rates, coupling reagents, bases, and coupling solution concentrations was conducted. From these studies, an efficient general continuous-flow peptide coupling protocol was established. With regards to previously reported methods the significant point of difference of the current procedure relates to formulating reagent concentrations based on the swollen resin volume. For both rink amide functionalised polystyrene and ChemMatrix resins, a 0.3 M amino acid and HATU matrix concentration, with a 5 mL min −1 flow rate at 60 °C promoted amino acid couplings and post coupling washes within 2.5 min. This racemisation-safe protocol also afforded the 65–74 sequence of the acyl carrier protein and a 29-mer segment of growth hormone-releasing hormone analogue in ≈85% crude purities.